2021
DOI: 10.1111/cas.14916
|View full text |Cite
|
Sign up to set email alerts
|

ZNF213 negatively controls triple negative breast cancer progression via Hippo/YAP signaling

Abstract: Breast cancer is one of the most commonly diagnosed malignancies worldwide, while the triple negative breast cancer (TNBC) is the most aggressive and virulent subtype in breast cancers. Compared with luminal type breast cancers, which could be well controlled by endocrine treatment, TNBC is worse in prognosis and lack of effective targeted therapy. Thus, it would be interesting and meaningful to identify novel therapeutic targets for TNBC treatments. Recent genomic data showed the activation of Hippo/YAP signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…In previous studies, we characterized several E3 ubiquitin ligases involved in modulating Hippo signaling effectors and cancer progression, such as RNF187 and ZNF213 [ 20 , 24 ]. However, protein stability is controlled by the balance between ubiquitination and deubiquitination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, we characterized several E3 ubiquitin ligases involved in modulating Hippo signaling effectors and cancer progression, such as RNF187 and ZNF213 [ 20 , 24 ]. However, protein stability is controlled by the balance between ubiquitination and deubiquitination.…”
Section: Discussionmentioning
confidence: 99%
“…Disrupted regulation of protein ubiquitination could contribute to several human diseases, including cancers [19]. We and other groups discovered several E3 ubiquitin ligases that exert their effects on Hippo pathway effectors and modulate Hippo signaling activity and cancer progression [20][21][22][23][24][25]. Although there are studies reporting the involvement of several deubiquitinases in modulating Hippo signaling, it is still largely unclear which of these deubiquitinases exerts important impacts on Hippo signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Ubiquitination, one of the most essential posttranslational modifications (PTMs), has been reported to have implicationse in a wide range of crucial cellular biological processes including signal transduction (Ben‐Dov et al, 2014; Zhou et al, 2021). In organisms, several important signaling pathways such as Wnt (Novellasdemunt et al, 2020; Shen et al, 2021), nuclear factor kappa B (Azuma et al, 2021), and Hippo (Liu et al, 2021) are regulated by ubiquitin ligase‐mediated ubiquitination in different cellular processes. Similar to other PTMs, such as phosphorylation and acetylation, protein ubiquitination is also a reversible process.…”
Section: Introductionmentioning
confidence: 99%
“…Although the activity of Hippo signaling is tightly controlled through the phosphorylation cascade, it is mysterious that YAP protein is over-active, even the Hippo signaling is still functional [ 25 ]. Besides phosphorylation, several other post-translational modifications were found to play critical roles in modulation YAP protein stability and function[ 23 , 26 , 27 ]. Our previous studies revealed a few E3 ubiquitin ligases, which modulated YAP protein ubiquitination via different mechanisms [ 10 , 11 , 23 , 26 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides phosphorylation, several other post-translational modifications were found to play critical roles in modulation YAP protein stability and function[ 23 , 26 , 27 ]. Our previous studies revealed a few E3 ubiquitin ligases, which modulated YAP protein ubiquitination via different mechanisms [ 10 , 11 , 23 , 26 , 28 ]. RBCK1 (RANBP2-type and C3HC4-type zinc finger-containing 1) belongs to the RING finger family and is composed of 510 amino acids [ 29 ].…”
Section: Introductionmentioning
confidence: 99%